Total alkalinity (TA) and dissolved inorganic carbon (DIC) in the Ems Estuary in 2020 - Norbisrath, Mona; van Beusekom, Justus; Thomas, Helmuth (PANGAEA, 2023)
We measured total alkalinity (TA) and dissolved inorganic carbon (DIC) in the Ems Estuary (Germany). The cruise took place on two consecutive days in June 2020 (11.06.-12.06.2020) on the German research vessel Ludwig Prandtl. We sampled approx. every 20min along the salinity gradient from the Wadden Sea around Borkum island upstream to Papenburg. Two additional samples were collected from shore at Rhede Brücke and weir Herbrum. We took discrete water samples for TA and DIC. Physical parameters (salinity, temperature) were measured in situ with the on board flow-through FerryBox system, for which water was pumped on board from 1.2m below the surface. These data and complementary data for nutrients and stable nitrate isotopes are accessible in: https://doi.org/10.1594/PANGAEA.942222